Analysis of the physical condition of popda athletics athletes of tanah laut regency - Gilang; Akhmad Amirudin; Perdinanto (Pendidikan Jasmani, Kesehatan, dan Rekreasi Universitas Nahdlatul Ulama Sunan Giri, 2025)
This study aims to analyze the physical condition of athletes in Popda Athletics Tanah Laut district which focuses on the physical condition of endurance athletes. Good physical condition can affect an athlete's ability to compete, so it is the basis for developing optimal techniques and tactics. Research methods using descriptive quantitative approach method. The population in this study is athletic athletes Popda Pasi Kabutpaten Tanah Laut with a sample of 18 athletes with a total sampling technique. The data were taken through Te lari 2.4 (cooper) which was held at Pertation Kencana Stadium. The results of the study were 1 person in the category very well and trained with a percentage (5.55%), very good at 1 person with a percentage (5.55%), good at 7 athletes with a percentage (38.88%), being 5 athletes with a percentage (27.77%), less than 4 athletes with a percentage (22.22%), and very less there were 0 athletes with a percentage (0%). The conclusion of the study found that the physical condition of the Popda Pasi athletics athletes Tanah Laut Regency was classified as good which showed that overall, the athletes had sufficient basic fitness to undergo training and competition. Further studies are advised to assess other components of physical condition such as muscle strength, speed, agility, and flexibility in order to provide an overall picture of the athlete's physical readiness.